(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2024)
The study aimed to describe how nature describes the character’s personality in Wuthering Heights novel and the writer also wants to convey the moral message contained in the novel with the aim that readers can implement it in everyday life. In order to keep the research focus thorough and in-depth, this research uses qualitative research. The method used in the research use a descriptive research. The theory used is the theory of literary eco-criticism. Researchers also applied a careful reading strategy to facilitate researchers in obtaining data. This research finds that the novel Wuthering Heights had explained that nature often describes the personalities of the characters such as wilderness, dwelling, and animal characters. In this novel, there are also moral messages conveyed such as religion, democracy, self-introspection, mutual respect, and social care. The message conveyed can also be implemented by readers in their daily lives.